2020
DOI: 10.1155/2020/8844052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Analyzing Techniques in Identifying Rainfall Trends for Colombo, Sri Lanka

Abstract: Identifying rainfall trends in highly urbanized area is extremely important for various planning and implementation activities, including designing, maintaining and controlling of water distribution networks and sewer networks and mitigating flood damages. However, different available methods in trend analysis may produce comparable and contrasting results. Therefore, this paper presents an attempt in comparing some of the trend analysis methods using one of the highly urbanized areas in Sri Lanka, Colombo. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Increasing trends for annual rainfall were identified in Colombo in previous studies (Malmgren et al 2003). Increasing trends during the NEM season in Colombo demonstrated in this study are in-lined with the finding of Perera et al (2020). The increasing trends in annual rainfall in Galle, Colombo, and Katunayake are similar to the direction of trends observed by Amarasinghe (2020).…”
Section: Trend Analysis Of Historical (1990 To 2019) and Future (2020...supporting
confidence: 91%
“…Increasing trends for annual rainfall were identified in Colombo in previous studies (Malmgren et al 2003). Increasing trends during the NEM season in Colombo demonstrated in this study are in-lined with the finding of Perera et al (2020). The increasing trends in annual rainfall in Galle, Colombo, and Katunayake are similar to the direction of trends observed by Amarasinghe (2020).…”
Section: Trend Analysis Of Historical (1990 To 2019) and Future (2020...supporting
confidence: 91%
“…The statistical trend was computed by using the Zc value. A positive value of Zc indicates an upward, and a negative indicates a downward trend (Perera et al 2020). The statistic Zc has a normal distribution to test for either an upward or downward trend at α level of significance (usually 5% ±Z1-α/2 = 1.96) (Gocic and Trajkovic 2013;Perera et al 2020)).…”
Section: Mann-kendall (Mk) Testmentioning
confidence: 99%
“…Several studies, including Abeysingha [27], Perera et al [28], Alahacoon and Edirisinghe [29], and Ruwangika et al [30], studied rainfall and streamflow trends in Sri Lanka. These studies identified an increasing rainfall trend over the country that was most prominent in the eastern, southeastern, north, and north-central areas.…”
Section: Introductionmentioning
confidence: 99%